The Significance of Choice in the Late Dorset Technology of Domestic Architecture - Ryan, Karen
This dissertation investigates the domestic architecture produced by the Late Dorset, an Arctic-adapted hunter-gatherer society which occupied much of the Eastern North American Arctic between circa 1500 B.P. and 500 B.P. Architecture, like any artefact class, is a dynamic and socially constructed technology that is produced, maintained, and transmitted by its practitioners. It is replicated via series of learned actions or techniques; patterns accordingly result from adherence to cultural standards while differences represent instances of technological divergence. Such departures are typically ignored or suppressed in closed systems, although they can be tolerated or even widely adopted in more flexible ones. In order to identify and explore patterning, a methodological strategy using the chaîne opératoire is adopted. This approach is invaluable because, when properly implemented, it links the static archaeological record with the dynamic architect-agents whose meaning-laden technical acts are visible archaeologically. Viewed through the lens of chaîne opératoire, I examine domestic architecture as a conduit for informing on Late Dorset structure and social organisation. As part of this investigation, a multi-scalar research design was implemented. The first analytical scale examined architecture across the Eastern Arctic to determine regional patterns of behavioural variability. Large-scale behavioural trends were recognised and demonstrated the range of behaviours enacted by Dorset architects as they designed, reproduced, and altered dwellings. The second stage of analysis focused on the micro-scale analysis of dwellings from three locations, each presented as fully contextualised case studies. Analysis at this level allowed for the investigation of how idiosyncratic behaviours and localised knowledge (reflecting an agent’s awareness of local conditions) was manifested and ‘fit’ within the overall technology. This strategy, which combined structure-specific analysis with purposefully broad regional patterning, suggests that Late Dorset architectural technology was comparatively open and flexible and that architects could adapt technological practise to suit local conditions and housing needs. This flexibility contrasts with other aspects of Late Dorset culture that appear more constrained and standardised. PhD